Hamlet - Shakespeare, William, 1564-1616; Edited By Taylor, Neil and Thompson, Ann (London Bloomsbury, 2014)
Thompson and Taylor offer an illustrated introduction to the play's historical, cultural and performance contexts, and a survey of critical approaches to the play.
Include Appendix, References and Index
Keywords: Hamlet (Legendary character)